2021
DOI: 10.1101/2021.07.05.21260021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude, and practice related to the COVID-19 pandemic among undergraduate medical students in Indonesia: a nationwide cross-sectional study

Abstract: Introduction. The potential role of medical students in raising awareness during public health emergencies has been acknowledged. To further explore their potentials as public educators and role models for the communities during the coronavirus disease 2019 (COVID-19) pandemic, a study is conducted to assess the knowledge, attitude, and practice of these students toward COVID-19. Methods. An online cross-sectional survey was conducted among undergraduate medical students in Indonesia. Socio-demographical chara… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Our findings also demonstrated positive correlations between knowledge-attitude, knowledge-practice, and attitude-practice, which were consistent with the literature data [ 17 , 29 ]. Many studies have reported the importance of KAP in society to reduce the spreading rate of infection during pandemics and epidemics [ 24 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings also demonstrated positive correlations between knowledge-attitude, knowledge-practice, and attitude-practice, which were consistent with the literature data [ 17 , 29 ]. Many studies have reported the importance of KAP in society to reduce the spreading rate of infection during pandemics and epidemics [ 24 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…They gain knowledge and understanding of different diseases during preclinical training. Hence, this group exhibits higher awareness of preventative measures for COVID-19 [ 29 ]. Additionally, many medical students involved themselves in managing COVID-19 patients during the pandemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Fauzi et al, 2020). In addition, the other researchers also found that students' knowledge about the pandemic was still less satisfactory (Adli et al, 2022;Sondakh et al, 2022). Nevertheless, such a finding did not align with other foreign research showing that students could identify whichever information based on natural science falls into fake news about the COVID-19 (Puig et al, 2021).…”
Section: Resultsmentioning
confidence: 80%
“…The low level of students' disbelief in those conspiracies was consistent with previous research reporting that level of literacy on COVID-19 phenomena demonstrated by Biology students in Indonesia was still low(Fauzi et al, 2020). In addition, the other researchers also found that students' knowledge about the pandemic was still less satisfactory(Adli et al, 2022;Sondakh et al, 2022). Nevertheless, such a finding did not align with other foreign research showing that students could identify whichever information based on natural science falls into fake news about the COVID-19(Puig et al, 2021).Regarding students' responses, CT on the pharmaceutical industry constituted the most believed conspiracy among the students.…”
mentioning
confidence: 77%
“…If the public responds or responds positively, then health protocols will also be applied regularly and adequately. And if the attitude is negative, then the response to information and the application of health protocols is also less such as not wearing a mask, not keeping a distance, and not paying attention to the COVID-19 outbreak (15)(16)(17)(18)(19). In this background, researchers are interested in doing research related to identifying knowledge, attitudes, and preventive behaviours in office workers about the prevention of COVID-19.…”
Section: Covid-19 Was Designated An Internationalmentioning
confidence: 99%